2016
DOI: 10.19183/how.23.1.299
|View full text |Cite
|
Sign up to set email alerts
|

How Novice EFL Teachers Regulate Their Negative Emotions

Abstract: This research report shares the findings that emerged from a qualitative study in which the main objective was to discover whether or not novice English as a foreign language teachers regulate their negative emotions during their initial teaching practice, and if so, how they do this. The data were collected by semi-structured interviews and observations, and analyzed by microanalysis and constant comparative analysis. The participants were five novice teachers who study English at the same university, and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…Finally, they experienced the interaction with administrators as encouraging and inspiring. Tejeda et al (2016) pointed out that EFL teaching is full of emotional labor, and their research confirmed that beginning EFL teachers reduce the influence of negative emotions through emotion regulation. Drawing on data from semistructured interviews and observations, they summarized the strategies five EFL teachers in Mexico used for emotion regulation, including selecting situations, cognitive change, modifying the emotional experience and expression.…”
Section: Empirical Studies On Efl Teachers' Emotional Labor Strategiesmentioning
confidence: 95%
“…Finally, they experienced the interaction with administrators as encouraging and inspiring. Tejeda et al (2016) pointed out that EFL teaching is full of emotional labor, and their research confirmed that beginning EFL teachers reduce the influence of negative emotions through emotion regulation. Drawing on data from semistructured interviews and observations, they summarized the strategies five EFL teachers in Mexico used for emotion regulation, including selecting situations, cognitive change, modifying the emotional experience and expression.…”
Section: Empirical Studies On Efl Teachers' Emotional Labor Strategiesmentioning
confidence: 95%
“…Negative emotions are usually experienced by preservice teachers because of students' poor participation, passiveness, noisiness, lack of motivation, and tiredness among other aspects (Nguyen, 2018). Although Gu and Day (2007) found that pre-service teachers with a teaching vocation are more resilient to negative experiences, negative emotions are also experienced by pre-service teachers who have the calling for teaching (Arizmendi Tejeda et al, 2016). Nevertheless, pre-service teachers with a vocation tend to see negative emotions in an optimistic way, which prevent them from losing energy and motivation (Cross & Hong, 2012).…”
Section: Emotions Of English Language Teachersmentioning
confidence: 99%
“…Two studies focused on Mexican pre-service teachers were analysed. Arizmendi Tejeda, Gillings de González, and López Martínez (2016) investigated if novice teachers used strategies to regulate the negative emotions experienced during practicum. They used observations and semi-structured interviews to collect data.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also influence their decisions, conduct, attitudes, actions and reactions. Therefore, humans find it impossible to separate emotions from actions and base their acts on logic alone (Rodrigo-Ruiz, 2016;Smith & Firth, 2018;Arizmendi Tejeda, Gillings de Gonzalez & Lopez Martinez, 2016). Benesch (2017, p.16) stated that "emotions are innate but originate in the brain and allow human beings to respond to the challenges of their daily life.…”
Section: Introductionmentioning
confidence: 99%